Visual art as a way to communicate climate change: a psychological perspective on climate change–related art. Issue 1 (2nd January 2018) - Roosen, Liselotte J.; Klöckner, Christian A.; Swim, Janet K.
Abstract : This article discusses the possible effects of climate change–related visual art, based on a comprehensive review of the psychological research literature. Taking a psychological perspective, potential effects of confrontation with such works of art are explored and a preliminary conceptual framework is proposed about special features of art that go beyond other means of communication. Potential barriers to change are discussed, as well as promising and often overlooked aspects that can trigger long-term changes, such as inspiration. Perceiving art demands attention, and processing art requires parts of the brain that are not normally accessed by typical communications about climate change. Art typically uses novel metaphors, analogies or narratives, which climate communication generally lacks. In addition, art can provide people with visualizations of the problem and give them a personal experience with the subject-matter, which is especially important regarding climate change as many people still see it as an abstract issue that poses no direct threat. Art may also help to establish a group identity and to give people a sense of being supported in their efforts to help combat climate change.